2008
DOI: 10.1021/ma800731r
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Polyoxymethylene: Spinning Conditions and Its Consequent Nanoporous Nanofiber

Abstract: A successful electrospun polyoxymethylene (POM) nanofiber using a hexafluoroisopropanol (HFIP)based solvent is reported. The nanofibers obtained show a significant nanoporous surface as a consequence of the spinning conditions, i.e. spinning voltage and relative humidity, as well as the polymer/solvent properties. The oxyethylene unit in the polyoxymethylene copolymer decreases the nanofiber surface roughness and porosity, leading to a significant change in the specific surface area. A slight change in the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 28 publications
2
77
1
Order By: Relevance
“…The high boiling point of DMF and high viscosity of HFIP solution might suppress phase separation during the solvent evaporation. 10 Surface modification of the electrospun nonwoven nanofiber mat was conducted by surface-initiated copper-catalyzed ATRP of hydrophilic DMAPS in methanol/water (14/86, v/v) solution at 30°C for 3 h and hydrophobic FA-C 8 in a bulk state at 60°C for 3 h (Scheme 1).…”
mentioning
confidence: 99%
“…The high boiling point of DMF and high viscosity of HFIP solution might suppress phase separation during the solvent evaporation. 10 Surface modification of the electrospun nonwoven nanofiber mat was conducted by surface-initiated copper-catalyzed ATRP of hydrophilic DMAPS in methanol/water (14/86, v/v) solution at 30°C for 3 h and hydrophobic FA-C 8 in a bulk state at 60°C for 3 h (Scheme 1).…”
mentioning
confidence: 99%
“…It was also reported that the oxyethylene units in the polyacetal copolymer decreased the nanofi ber surface roughness and porosity, leading to a signifi cant change in the specifi c surface area, as presented on Figure 14.34 [121]. Moreover, a decrease in nanoporosity could be achieved under a decrease of solvent vapor pressure, an increase of spinning voltage, and a decrease of relative humidity.…”
Section: Pom Nanostructures -Electrospun Pom Nanofi Bersmentioning
confidence: 82%
“…34 Scanning electron micrographs of the electrospun POM nanofi bers from an HFIP solution with copolymer contents of (a) 0, (b) 1.5, (c) 4.4, and (d) 13 wt% (electrostatic fi eld strength ) 15 kV/10 cm and relative humidity (75%)[121].…”
mentioning
confidence: 99%
“…The decrease in the surface temperature for the polymer solution would lead to thermally induced phase separation. [31][32][33] Second, the condensation of atmospheric moisture may have induced phase separation. This moisture would condense at the outermost surface of the sprayed polymer solution as its surface temperature decreases.…”
Section: Results and Discussion Preparation Of The Electrospun Non-womentioning
confidence: 99%